Housing consumption and macroprudential policies in Europe: An ex ante evaluation - Antonios Mavropoulos; Qizhou Xiong (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
In this paper, we use the panel of the first two waves of the Household Finance and Consumption Survey by the European Central Bank to study housing demand of European households and evaluate potential housing market regulations in the post-crisis era. We provide a comprehensive account of the housing decisions of European households between 2010 and 2014, and structurally estimate the housing preference of a simple life-cycle housing choice model. We then evaluate the effect of a tighter LTV/LTI regulation via counter-factual simulations. We find that those regulations limit homeownership and wealth accumulation, reduces housing consumption but may be welfare improving for the young households.
urn:nbn:de:gbv:3:2-97162
Keywords: D14; D31; D91; 330; housing consumption; macroprudential policies; LTV/LTI regulation